2023
DOI: 10.3390/ph16070928
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Grape Leaf Extract Reduce Eimeriosis-Induced Inflammation, Oxidative Status Change, and Goblet Cell Response in the Jejunum of Mice

Abstract: Coccidiosis is a parasitic infection threatening poultry products globally. Parasite resistance to drugs is one of the barriers to Eimeria control. Natural products are one of the sources of compounds that prevent parasite infections. The current study was, therefore, conducted to evaluate the effect of Vitis vinifera leaf extract on anti-inflammatory response, oxidative status, and goblet cell response against Eimeria papillate infection in mice. Methanol was used as a solvent for phytochemicals. The mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The coccidial infection disturbs the work of the antioxidant defense system against free radical generation (Murshed et al, 2023) . Our results demonstrated that infection with E. tenella is linked to oxidative stress in broiler chickens' cecum, reducing the levels of GSH, GPx, and SOD enzymes, and these antioxidant defense systems are essential for preventing free radical damage to the animal body during an Eimeria infection.…”
Section: Discussionmentioning
confidence: 99%
“…The coccidial infection disturbs the work of the antioxidant defense system against free radical generation (Murshed et al, 2023) . Our results demonstrated that infection with E. tenella is linked to oxidative stress in broiler chickens' cecum, reducing the levels of GSH, GPx, and SOD enzymes, and these antioxidant defense systems are essential for preventing free radical damage to the animal body during an Eimeria infection.…”
Section: Discussionmentioning
confidence: 99%